THE COMMUNITY'S VIEW ON THE OPENING OF THE BORNEO CULTURES MUSEUM AS A TOURIST ATTRACTION - Ai Kee, Lau; Shaik Azahar, Shaik Hussain (Researchgate, 2023)
The purpose of this study is to find out the community's views on the opening of the Borneo Cultural Museum as a tourist attraction. Borneo Cultures Museum is a treasure of Sarawak's cultural and historical wealth as well as Borneo's cultural treasures. The researcher focused on three objective studies, namely to identify the causes of parking congestion that occur at the Borneo Cultural Museum, to study the public's view of the Borneo Culture Museum and to analyze the importance of community involvement in the heritage tourism industry to the Borneo Cultural Museum. The methodology used by the researcher is a quantitative method. As a result, this study was conducted to collect all information and data about community satisfaction to the Borneo Cultural Museum. Overall, the data provided by the respondents was able to solve the problem and achieve the objectives of the study.